Metastasectomy in kidney cancer: current indications and treatment approaches. Issue 4 (December 2021) - Prunty, Megan; Bukavina, Laura; Psutka, Sarah P.
Abstract : Purpose of review: Although systemic agents for the treatment of metastatic renal cell carcinoma (mRCC) have improved survival, remission and cure for mRCC remains rare with systemic therapy alone. However, there is a body of observational evidence supporting a survival benefit in mRCC among patients who undergo complete surgical consolidation including resection of the primary tumor and all metastatic deposits. In this review, we aim to synthesize recent evidence regarding metastasectomy (MTS), with or without concurrent systemic therapy, in mRCC. Recent findings: MTS is a critical component of mRCC patient care, alongside modern systemic therapy. Presently, there is a robust body of observational data supporting the association between surgical MTS and improved oncologic outcomes, especially when complete MTS is feasible. Summary: Among a retrospective, observational body of literature, MTS is associated with improved oncologic outcomes. However, it is impossible to discern to what degree these findings are biased by favorable tumor biology and patient selection, as opposed to being related to surgical MTS itself.